(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Now-a-days internet has become one of the basic aids for day-to-day living. Every human being is widely accessing the knowledge, information and also using for communication through internet. However, blind people face difficulties in accessing these net-based information, also in using any service provided through internet. The advancement in computer based accessible systems has opened up many possibilities for the visually impaired across the worlds in a wide way. Audio based virtual environment like, the screen readers and many voice-based search engines have helped Blind people to access internet applications immensely. We describe the Voice-based mail system architecture that can be used by a Blind person to access e-Mails easily and efficiently. The contribution made by this research has enabled the Blind people to send and receive voice-based e-Mail messages with the help of a computer.